IN SILICO DESIGN, SYNTHESIS, CHARACTERIZATION, IN VITRO ANTI-INFLAMMATORY, AND ANTIOXIDANT STUDIES OF 4-ARYL-4H-CHROMENE DERIVATIVES - Rajan, Jithila; Krishnan, Saranya; Menon, Sruthi V; Zachariah, Subin Mary; Pai, Rajasree G; M, Surya; Javahar, Muhammed; George, Namy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of the study was to explore in silico design, preparation, characterization, and evaluation in vitro of some novel 4H-chromene derivatives as anti-inflammatory and antioxidant agents. Methods: 4-phenyl-4H chromene derivatives were imperiled to in silico modeling studies at the molecular level. The ligands were docked against cyclooxygenase-2 (COX-2) receptor targets using Argus Lab. Based on the result, the derivatives were selected for wet lab synthesis. A highly efficient multicomponent reaction of 4H chromene was carried out by one-step condensation of aldehyde with malononitrile and resorcinol without catalyst in water under ultrasound irradiation. The prepared compounds were characterized by noting their melting point, ultraviolet (UV) spectroscopy, infrared (IR) spectroscopy, and thin layer chromatography (TLC) and were scrutinized for its in vitro anti-inflammatory and antioxidant activitives by in vitro cell culture studies. IR spectra of the two compounds were analyzed and studied. Thus, using melting point, TLC and UV spectroscopy the synthesized compounds were found to be pure and identified chemically. The synthesized compounds were then screened for in vitro antioxidant (by 2,2-diphenyl-1-picrylhydrazyl (DPPH) and hydrogen peroxide free radical scavenging) activity and anti-inflammatory activity by Raw 264.7 cell lines. Result: From the study, it was noticed that chemical structure-2 showed better antioxidant and anti-inflammatory activitives than chemical structure. In the 4-phenyl-4H chromene derivatives, hydroxyl substitution at 7th position and electronegative halogen at 4th position showed better antioxidant and anti-inflammatory activities. Conclusion: The results disclosed that these synthesized derivatives be likely to have moderate action against COX-2 mediated diseases, thereby it may lessen inflammation and agony because of its antioxidant and anti-inflammatory activitives.